2019
DOI: 10.1007/s00167-018-5338-z
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic primary repair of proximal anterior cruciate ligament tears: outcomes of the first 56 consecutive patients and the role of additional internal bracing

Abstract: PurposeRecent outcomes of arthroscopic primary repair of proximal anterior cruciate ligament (ACL) tears have been promising in small cohort studies. The purpose of this study was to assess outcomes of arthroscopic ACL repair in a larger cohort and to assess the role of additional augmentation. MethodsThe first 56 consecutive patients that underwent arthroscopic ACL repair were examined at minimum 2‐year follow‐up. The latter 27 patients [48.2% (27/56)] received additional internal bracing with ACL repair. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
164
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(173 citation statements)
references
References 49 publications
(86 reference statements)
4
164
1
4
Order By: Relevance
“…reported outcomes at medium-to long-term follow-up (range of mean follow-up 43.3-79 months) 41,48,49,52 including the mean IKDC subjective score (range 87.3-100), the mean Lysholm score (range 85.3-100), and the mean Tegner activity score (range 5-7). The remaining 10 studies 36,40,[42][43][44][45][46]50,51,53 reported the same outcome measures at short-term follow-up (range of mean follow up 12-38.4 months). At final follow-up, these studies reported a mean IKDC subjective score of 89.5-98, a mean Lysholm score of 93-100, and a mean Tegner activity score of 5-7.…”
Section: Clinical Outcomes Reported In Comparative Studiesmentioning
confidence: 93%
See 4 more Smart Citations
“…reported outcomes at medium-to long-term follow-up (range of mean follow-up 43.3-79 months) 41,48,49,52 including the mean IKDC subjective score (range 87.3-100), the mean Lysholm score (range 85.3-100), and the mean Tegner activity score (range 5-7). The remaining 10 studies 36,40,[42][43][44][45][46]50,51,53 reported the same outcome measures at short-term follow-up (range of mean follow up 12-38.4 months). At final follow-up, these studies reported a mean IKDC subjective score of 89.5-98, a mean Lysholm score of 93-100, and a mean Tegner activity score of 5-7.…”
Section: Clinical Outcomes Reported In Comparative Studiesmentioning
confidence: 93%
“…The most frequent reoperation was ACL reconstruction. Hoffman et al 49 reported an ACL reconstruction rate of 16.7% at a mean follow-up of 79 months, and Jonkerouw et al, 46 7.1% at 38 months. In the only study that compared outcomes of ACL repair with and without IB, Jonkerouw et al 46 reported that there was no significant difference in the failure rate between repairs performed with IB (2/27; 7.4%) and those without (4/29; 13.8%, P ¼ .672).…”
Section: Clinical Outcomes Of Noncomparative Studiesmentioning
confidence: 97%
See 3 more Smart Citations